COLLECTIVE METHODS OF MANAGEMENT DECISION-MAKING AS A TOOL FOR IMPROVING MANAGEMENT EFFICIENCY - Bondarchuk , N.V. (The actual problems of regional economy development, 2021)
The article is aimed at the study of collective methods of management decision-making. The purpose of the article is to study the process of managerial decision-making and determine the main collective methods of managerial decision-making. The research methods used in the process of writing the article involve the use of general scientific and empirical techniques of economics, based on a systematic approach. The article states that decision-making is a conscious choice of available options or alternatives. This process includes many different elements, but it certainly has such elements as: problems, goals, alternatives and their own solutions. The article considers the theoretical foundations of management decisions, methods of management decisions. The main features of the management decision are determined, which include: the choice of alternatives and the act of will. In the course of the research it was stated that the term "management decision" is used in two main meanings: as a process and as a phenomenon. Attention is also paid to a number of factors that are taken into account when making management decisions. The article theoretically substantiates the recommendations for improving the development of management decisions. In particular, the algorithm of management decision-making is offered, which consists of the following stages: situation analysis, definition of the problem to be solved, development of alternatives, delineation of evaluation criteria, evaluation of efficiency of alternative solutions, selection of the best management decision, control over management decision and analysis of the obtained results. The article identifies group decision-making methods that are used to justify management decisions, including: Hoya-Tarter decision-making model, Multiple voting method, Modified Board method, CODM, RAPID, etc. Features of modern conditions of decision-making and properties of such conditions are outlined. It is noted that the creative work of the decision-making enterprise and its administrative staff requires certain skills, as well as the use of separate decision-making tools. The practical significance of this article is that the use of the outlined group methods of management decision-making will increase the efficiency of management, as well as reduce the risks that arise in the process of enterprise activity.